GENDER EQUALITY AND DIVERSITY - Kachhap, Rahul Vincent (2015)

(untitled)
Gender equality has always been considered as a social issue in India. In a way this has created an unconscious biasness for female at workplace. Women have always been considered as homemakers and have been given a secondary status both at home and workplace. There are also other barriers and gaps that have not allowed women to climb at top-level positions in organisations.